Measuring Results & the DCED Standard - Tanburn, Jim (2014)
This page gives an introduction to the DCED Standard, which is a framework that helps practitioners to measure results in Private Sector Development (PSD).

Measuring Impact: A Learning Approach to Strengthening USAID Biodiversity Programs - Lauck, Liz (2014)

Complexity-Aware Monitoring Discussion Note (Screencast) - Patsalides, Melissa; Britt, Heather (2014)
This screencast covers information included in the Complexity-Aware Monitoring Discussion Note. The topic is intended for those seeking cutting-edge solutions to monitoring complex aspects of strategies and projects. Most of the principles and promising approaches discussed here have a significant body of theory and practice behind them, but many have not been used to monitor USAID strategies and projects. We have much to learn about whether and how they can be applied successfully in the Agency. USAID's Office of Learning, Evaluation, and Research in the Bureau of Policy, Planning, and Learning has partnered with different groups through monitoring trials to build a body of evidence regarding which complexity-aware M&E approaches are most effective in the contexts of USAID programming.

USAID’s Data Quality Standards & Conducting a DQA - USAID (2014)